Sturge Weber Syndrome Overlapping with Klippel Trenaunay Syndrome - Sarkar, Shatanik; Patra, Chaitali; Dey, Chandrasekhar; Dasgupta, Malay Kumar; Kundu, Tapan Kumar (Journal of Nepal Paediatric Society, 2013)
Sturge Weber syndrome (SWS) is a mesodermal phakomatosis characterized by meningo-facial angiomas with cerebral calcification. Klippel Trenaunay syndrome (KTS) is another very rare type of phakomatosis with cutaneous angiomas, varicose veins and enlargement of soft tissue or bones. Overlap between SWS & KTS is very rarely encountered. We report a three and half year old girl with overlapping features of both SWS and KTS. DOI: http://dx.doi.org/10.3126/jnps.v33i2.7704 J Nepal Paediatr Soc. 2013; 33(2):147-149